Avoidance of bus bunching - Priyadarshini, Ramasamy (2018)
Bus bunching is the phenomenon of clumping / clustering of buses. Generally buses are scheduled and expected to operate at certain time intervals on a specific route. It is of a natural occurrence that the due to on-road delays and other reasons, the buses deviate from the schedule. This results in decreasing the headway time and hence the buses bunch among themselves. The scope of the work done is to design a decentralized control mechanism, which allows buses to maintain a fixed headway gap among them. The gap wouldn’t let the buses to bunch and hence serve the stops and the passenger at those stops at equal intervals. The controller designed has been checked using MATLAB. The microscopic simulator VISSIM has been used to test the efficacy of the controller on a real time road network.